102 Means to Prevent Microbial Enteric Pathogens Transmission through Animal Food. (10th April 2018) - Li, X; Benjamin, L; Edwards, D; McChesney, D
Abstract: Animal food (pet food and animal feed) can become contaminated with microbial enteric pathogens. These contaminants may present a hazard to animal health by consumption of the animal food and to human health by consumption of animal-derived human food or by exposure to a contaminated animal food. The U.S. Food and Drug Administration's (FDA) Center for Veterinary Medicine conducts surveillance of microbial contamination in pet food and animal feed. A current high priority for surveillance testing is the enteric pathogen Salmonella . Additional enteric pathogen in raw pet food includes Listeria monocytogenes in 2015. Animal food samples of dry pet food, pet treats, nutritional supplement for pets, complete animal feed, and ingredients were randomly collected at the manufacturer, distributor, wholesaler, or retailer in the United States, or at the United States ports of entry and tested for the presence of Salmonella . Those that were positive for Salmonella underwent serotyping. Of the 2, 058 samples collected in 2002-2009, 259 were positive for Salmonella (12.5%), while of the 2, 963 samples collected in 2010-2014, 151 were positive for Salmonella (5.1%). The prevalence data indicate significant Salmonella reduction in animal food between the two timeframes. Among these samples, pet food and ingredients had the most significant reduction. The serotyping data indicate although the most common Salmonella serotypes found in humans were seldom found in animal food, some Salmonella serotypes found in animal food also were found in humans. In July 2013 FDA published Compliance Policy Guide (CPG) Sec. 690.800 Salmonella in Food for Animals. The CPG describes a risk-based enforcement strategy FDA uses to determine when to take enforcement action against animal food contaminated with Salmonella . FDA believes regulatory action is warranted in cases involving pet food contaminated with any Salmonella serotype. In cases of animal feed contaminated with Salmonella, FDA believes regulatory action is warranted when such cases involve Salmonella serotypes that are known to cause disease in the animal species. Because sources of microbial enteric pathogen contamination in animal food can be related to ingredients, processing, and facility, prevention of microbial enteric pathogen transmission through animal food to animals and humans should include supply-chain control, process control, and sanitation control.